COMPILATION OF MOMENTS OF SPIN MAXIMA OF THE INTERMEDIATE POLAR EX HYA - Breus, V. V.; Andronov, I. L. (Одеські астрономічні публікації, 2013)
We present a compilation of the spin maxima of the intermediate polar EX Hya determined using the same methods for our own observations from the Tzec Maun observatory, published observations from the SuperWASP, ASAS and AAVSO databases. For completeness, published data published by other authors are used. We obtained the ephemeris of the spin maxima Tmax=2437699.89079(59) +0.0465464808(69)E-6.3(2)10-13 E2, which corresponds to the characteristic time of acceleration of rotation (spin-up) of 4.67(14) 106 years.